Strengthening Transfer of Technology Among High Altitude Community of Ladakh (Indian Journal of Extension Education, 2013)
Different socio-cultural environment requires different method of technological interventions, so is true of cold-arid high altitude communities (HACs). In India, cold-arid HAC like Ladakh (J&K) and Lahoul Spiti (HP) has been neglected in this respect because of their lack of representation at national level due to their meager proportion in terms of population size. Though there has been considerable interest shown by social scientists in understanding the socio-cultural environment prevailing in these parts of the world, but there has been lack of interest among researchers to understand and contrive a model of technology intervention among such communities. This has resulted into the adoption of ’copy and paste’ model of technology intervention modalities, where models adopted for lowlanders were/are applied for HAC at various policy decision making platforms. Therefore an effort has been made through this paper to understand the various factors (both local and contextual) whose understanding would help extension workers and policy makers in increasing the efficacy and rate of technology transfer among HAC. Emphasis has been given to understand the prevailing local institutions, local wisdom and resource management practices and how these understanding could be applied in various extension activities for an effective technology transfer and intervention. The present study limit itself to Ladakh region due to accessibility constraints and the familiarity of the results.